(untitled) (UNED Research Journal, 2019)
Introduction: Costa Rica is the Central American country with the most bibliometric studies, however, very few on the historical trends of particular academic journals. Objective: We analyze the statistical trends of the first decade of the journal Cuadernos de Investigación UNED, considering four topics: who publishes, what they publish, how trends have varied over time and what we can expect in the future. Results: The number of frames per article was high at the beginning, then lower, oscillating stably between 2 and 3. The number of figures per article ranges from 2 to 5. The articles have tended to be shortened. The number of authors per article ranges from 2 to 3. Authors have oscillated between a third and a half. The six people with the highest total number of articles published are from the Universidad Estatal a Distancia (UNED), followed by the Universidad de Costa Rica (UCR); half, women. Articles on Costa Rica predominate, followed a long way by the rest of Latin America, Africa and Asia. Articles from Costa Rica have been quadrupled. As for the country of the authors, Costa Rica dominates strongly. The institutions that predominate as sources of articles are the UNED, UCR and the National University of Costa Rica (UNA). UNED has been stable, UCR every 5 years seems to increase, Universidad Nacional de México (UNAM) has decreased. Those who publish about Costa Rica are Costa Rican authors. Increase of articles in Spanish is more marked and constant. Conclusion: The historical patterns coincide with that of other scientific journals such as Tropical Biology that, although published in small countries, are inserted in the much wider world of international science.